2008
DOI: 10.1152/jn.00015.2008
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Recovery of Motor Memory During Saccade Adaptation

Abstract: It is possible that motor adaptation in timescales of minutes is supported by two distinct processes: one process that learns slowly from error but has strong retention, and another that learns rapidly from error but has poor retention. This two-state model makes the prediction that if a period of adaptation is followed by a period of reverse-adaptation, then in the subsequent period in which errors are clamped to zero (error-clamp trials) there will be a spontaneous recovery, i.e., a rebound of behavior towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
165
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(185 citation statements)
references
References 22 publications
10
165
0
1
Order By: Relevance
“…Multiple states models of saccadic adaptation have also been proposed by two other teams (Ethier et al, 2008b;Kojima et al, 2004). Both studies showed that the effect of an initial adaptation training can persist after saccade gain is brought back to its preadaptation level through de-adaptation (i.e., recovery).…”
Section: Multiple Adaptation Statesmentioning
confidence: 99%
“…Multiple states models of saccadic adaptation have also been proposed by two other teams (Ethier et al, 2008b;Kojima et al, 2004). Both studies showed that the effect of an initial adaptation training can persist after saccade gain is brought back to its preadaptation level through de-adaptation (i.e., recovery).…”
Section: Multiple Adaptation Statesmentioning
confidence: 99%
“…The idea was proposed by Smith et al (2006) to account for data obtained during adaptation of saccadic eye movements (Kojima et al 2004) and was further tested in adaptation of reaching movements in response to a force field perturbation (Smith et al 2006) and visuomotor rotations (Lee and Schweighofer 2009;Shmuelof et al 2012;Zarahn et al 2008). The model was successful in explaining many phenomena, such as savings, adaptation rebound (Smith et al 2006), spontaneous recovery (Ethier et al 2008), memory decay (Shmuelof et al 2012;Vaswani and Shadmehr 2013), and generalization (Tanaka et al 2012). Joiner and Smith (2008), using a force field adaptation paradigm, further suggested that the magnitude of retention at 24 h could be predicted by the amount by which the "slow" system had adapted: retention at 24 h reflected ϳ65% of the magnitude of adaptation of the slow process after adaptation with 11, 30, 103, and 160 trials.…”
mentioning
confidence: 99%
“…To quantify trial-by-trial learning from error, we analyzed the data using a state-space model of motor adaptation (Ethier et al 2008;Smith et al 2006). In this model, on trial n the participant is presented with a visual target at location t (n) .…”
mentioning
confidence: 99%